Development of biocomposite film from banana peel and corn starch incorporated with cinnamon essential oil / Fatin Nur Nabila Natasha Khairul Jamil, Mohamad Khairi Zainol and Azlin-Hasim Shafrina - Khairul Jamil, Fatin Nur Nabila Natasha; Zainol, Mohamad Khairi; Shafrina, Azlin-Hasim (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Utilization of the agricultural waste such as banana peel can help in reduce the rising environmental issues such as food waste and greenhouse gas emission. The purpose of this study is to develop biocomposite films from banana peel and corn starch incorporated with cinnamon essential oil (EO). The effect of the incorporation of cinnamon EO at different concentrations (1%, 3% and 5%) into banana peel and corn starch film on antimicrobial activity, mechanical properties and barrier properties were investigated and characterized. The properties of the developed films were tested using antimicrobial activity, thickness, colour analysis, mechanical properties, water vapour permeability (WVP) and water solubility test. It was found that the antimicrobial activity of the film significantly increased (p<0.05) with the increase of cinnamon EO concentration. The cinnamon EO had greater effect on Gram-positive bacteria (Staphylococcus aureus and Bacillus cereus) compared to Gram-negative bacteria (Salmonella and Escherichia coli). The L-value (lightness) of the film decreased with the increase of cinnamon EO. The thickness of the biodegradable films increased (p<0.05) with the addition of cinnamon EO; however, it also weakens the mechanical properties of the biocomposite films. This may due to the modification of structural positioning of the film matrix occurred with the addition of cinnamon EO, hence, resulted in brittleness and reduction strength of the biocomposite film. The WVP value of the film was not affected (p>0.05) with the addition of cinnamon EO. The water solubility of the film decreased (p<0.05) with the increased of cinnamon EO concentrations. This may be due to the hydrophobic nature of cinnamon EO. Overall, incorporation of cinnamon EO into the banana peel and corn starch biocomposite film improved its antimicrobial activity and barrier properties but weaken its mechanical properties.